2019
DOI: 10.1038/s41598-019-43754-x
|View full text |Cite
|
Sign up to set email alerts
|

Li(Cd,Mn)P: a new cadmium based diluted ferromagnetic semiconductor with independent spin & charge doping

Abstract: We report a new diluted ferromagnetic semiconductor Li 1+y (Cd,Mn)P, wherein carrier is doped via excess Li while spin is doped by isovalence substitution of Mn 2+ into Cd 2+ . The extended Cd 4 d -orbitals lead to more itinerant characters of Li 1+y (Cd,Mn)P than that of analogous Li 1+y (Zn,Mn)P. A higher Curie temperature of 45 K than that for Li 1+y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…在Li(Zn,Mn)As之后, 很快便有了其他"111" 型 稀 磁 半 导 体 的 研 究 , 包 括 Li(Zn,Mn)P以 及 Li(Cd,Mn)P等, 它们均与LiZnAs有着相同的晶 体结构和相似的能带结构, 基于同样的掺杂设计, 它们也同样因过掺杂的Li而成为一种p型半导 体. 对于Li(Zn,Mn)P来讲, 最高T C 为34 K, 且在 低温下具有与Li(Zn,Mn)As相当的饱和磁矩和同 样低的矫顽力(小于100 Oe), 但Li(Zn,Mn)P的 电导率始终随温度上升而下降, 即为半导体性; 同 时, Li(Zn,Mn)P也具有负磁阻, 最大超过-30% [24,25] .…”
Section: 着材料磁性是其具有的本征属性 明确地证明了unclassified
“…在Li(Zn,Mn)As之后, 很快便有了其他"111" 型 稀 磁 半 导 体 的 研 究 , 包 括 Li(Zn,Mn)P以 及 Li(Cd,Mn)P等, 它们均与LiZnAs有着相同的晶 体结构和相似的能带结构, 基于同样的掺杂设计, 它们也同样因过掺杂的Li而成为一种p型半导 体. 对于Li(Zn,Mn)P来讲, 最高T C 为34 K, 且在 低温下具有与Li(Zn,Mn)As相当的饱和磁矩和同 样低的矫顽力(小于100 Oe), 但Li(Zn,Mn)P的 电导率始终随温度上升而下降, 即为半导体性; 同 时, Li(Zn,Mn)P也具有负磁阻, 最大超过-30% [24,25] .…”
Section: 着材料磁性是其具有的本征属性 明确地证明了unclassified
“…The discovery of Li(Zn,Mn)As sparked extensive researches in this 111 type DMSs [28,[32][33][34][35][36] . Fig.…”
Section: Polycrystals Synthesis and Basic Physicial Properties 21 "11...mentioning
confidence: 99%
“…Masek et al firstly predicted that I-II-V Li(Zn,Mn)As could become a new diluted magnetic semiconductor [24] . In 2011, Deng et al successfully synthesized the samples and observed ferromagnetic ordering below the Curie temperature ~ 50 K [17] .…”
Section: -Systemmentioning
confidence: 99%